Ion Beam Mixing and Electrocatalysis of Platinum-Iron Alloys - Fernandes, Mark G. (My University, 1986)
The experiment work pertaining to this thesis can be divided into two parts: a) The study of the ion beam mixing process in the platinum-iron system and b) Electrocatalysis measuremnts on the mixed platinum-iron alloys. The ion beam mixing was studied using a 120 keV Fe+ ion over a rang of temperatures from 298K to 523K. A thin film of platinum was evaporated onto an oxide free substrate of iron to form a bi-layer sample. In order to check whether the interface was clean and oxide-free, Auger electron spectrometry was used along with sputtering. The mixing was studied primarily using RBS. The TEM was also used to characterize the samples before and after mixing.
At low temperatures (<373 K), the mixing is very small and found to take place by collisional processes. At higher temperatures (>473 K) iron moves rapidly into the platinum. The activation energy for the platinum migration into the iron was found to be ~0.5 eV. This suggests that the vacancy mechanism is operating about 423 K. The films produced by mixing at low temperatures are highly stressed and there are a considerable amount of twins formed. It was also found that the grain size increases with dose and temperature.
The surface concentration Pt in the mixed film is high ~90%. This results in an improvement of ~25% in the overvoltage for the ion beam mixed films compared to an iron electrode. Ion beam mixed films were found to be more stable than iron electrodes simply coated with films with an evaporated platinum layer. This appears to be the result of the improved adhesion between the platinum and iron as a result of the ion beam mixing process. For unmixed samples, an oxide layer is able to form on the iron surface at the platinum./iron interface, possibly because of cracks in the platinum layer, and this results in platinum pealing off the electrode leaving just the iron electrode.
Keywords: Materials Science and Engineering; Other Materials Science and Engineering; Materials Science and Engineering